Constructing Functional Models of Economic Phenomena by the Method of Statistical Equations of Dependences - Kulynych, О. І. (Statistics of Ukraine, 2017)
The functional theoretical model of the socio-economic development of regions is constructed by the method of statistical equations of dependences, for substantiating objectives, plans and standards. The nomenclature of factors with impact on the formation of gross regional product is proposed, the share of impact of each factor is determined. In the new economic conditions, the concept of planning is determined from the perspective of outlining the ways to achieve its effectiveness. The process of planning needs to consist of formulating overall strategic intentions on determining specific and detailed actions aimed at generating income and spending over a certain period (a year or five years), outlining the ways and means for the achievement of goals. An important component in this process is control over the achievement of the goal by comparing reported and planned data, identifying and evaluating factors with either positive or negative impact on the economic performance. Solutions to the issues of planning and forecasting of phenomena and processes, structural change in the economy or stability of the economic system are a matter of vital importance for scientific communities, practical economists and power officials. This is a reason behind great attention drawn to constructing of economic development models, designed to analyze allocation of production resources and distribution of the national product for social purposes, which constitutes the main function of the state policy Basically, economic and statistical modeling can be made by use of the following models: model of economic systems; model of production process; model of demand and consumption of goods and services; model of prices and income; model of financial flows; model of national economy; model of socio-economic development. When modeling the socio-economic development at country or regional level, constructing and evaluating social and economic policies at either level, statistical methods need to be used, expert methods and methods of neural-fuzzy modeling in particular. Use of the method of statistical equations of dependences allows for supplementing the given nomenclature of forms for economic and statistical modeling by the following types of modeling: substantiating the objectives, plans or standards of the development of economic phenomena through constructing of functional theoretical models; predicting change in the factors when determining the level of socio-economic phenomena in a future period. Understanding the essence of an economic model is greatly important for generating information about the socio-economic development.